Planned Behaviour in Purchasing Health Insurance - Brahmana, Rayenda; Brahmana, Ritzky Karina; Memarista, Gesti (UI Scholars Hub, 2018)
This research aims to investigate why there is low insurance purchasing in Indonesia. The research framework adopts the theory of planned behaviour in exploring the insurance purchase intention behaviour of Indonesians. Furthermore, this research introduces health value as the moderating variable on the relationship between attitude towards insurance purchasing and the intention to purchase insurance. We take 311 insurance holders from five Indonesian big cities as the sample. The results show that perceived risk and perceived usefulness play important roles in the attitude towards the intention to purchase health insurance. Our findings also show that health value contributes significantly in explaining health insurance purchasing. This research contributes to the body of knowledge by introducing the theory of planned behaviour in health insurance research. Moreover, this research suggests to policymakers or insurance companies how to gauge psychological factors in terms of influencing people to purchase health insurance.